The Role of Smart Boards in Improving the Motivation and Academic Performance of EFL University Students of Saudi Arabia - Swamy Chatta, Bala; Imdadul Haque, Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
With the advent of smart boards, the traditional teaching pedagogy of EFL class rooms has become more appealing and interesting for the students as well as the teachers. In order to motivate the students of Saudi Arabia to acquire English language skills, technology, which includes smart boards, is introduced in the classroom. Many studies show that Saudi students lack motivation to learn English due to various reasons. The present study aims at identifying the impact of smart boards on improving the motivation and performance levels of EFL students at Prince Sattam Bin Abdulaziz University. After identifying and classifying two groups of students, the smart board is used for the experimental group, and the white board is used for the control group. The treatment was given for eight weeks. A questionnaire was given, and the student responses were taken from the experimental group after the study. A group discussion was held with the students of the experimental group to understand deeply about the impact of the smart board on their motivational levels and performance in the exams. The results showed that there is a significant difference in the experimental group in terms of motivation and grades.